Does Dodd-Frank affect OTC transaction costs and liquidity? Evidence from real-time CDS trade reports - Loon, Yee Cheng; Zhong, Zhaodong (Ken) (Journal of Financial Economics, 2016)
This paper examines transaction costs and liquidity in the index CDS market by matching intraday quotes to real-time trade reports made available through the Dodd-Frank reforms. We find that the average relative effective spread is 0.27% of price level or 2.73% of CDS spread. Dodd-Frank does affect transaction costs and liquidity. Liquidity improves after the commencement of public dissemination of OTC derivatives trades. Moreover, cleared trades, trades executed on exchange-like venues, end-user trades, and bespoke trades exhibit lower trading costs, price impact, and price dispersion. These findings improve our understanding of the OTC derivatives market that is undergoing fundamental changes.